Educational ‘exchange rates’ in (re)settlement: The use of formal and informal learning resources by displaced people from Ukraine in Australia - Bogachenko, Tetiana; Burke, Rachel (International journal of educational research, 2024)
•Displaced people utilise an array of formal and informal learning resources to assist them in (re)settlement.•The capacity of these sources of knowledge to provide accurate and timely information impacts capital conversion/activation.•The conversion of different types of capital is neither a homogenous nor a linear process. It is cyclical and iterative.•The ‘exchange rates’ for successful conversion and activation of capital in the host country are not immediately clear.•Stakeholder collaboration and consulting with displaced people are key to understanding and supporting capital portfolios. Education—both formal and informal—is a fundamental human right and key to individual and community-level health, economic sustainability, and social and (trans)cultural engagement. While previous research has examined the challenges of pursuing education in the context of migration and (re)settlement, the value of education as capital and the complexities of converting this capital in emergency international displacement requires further investigation. We conducted a pilot study with displaced people from Ukraine who arrived in Australia after February 2022 to explore the uptake and use of both formal and informal learning resources and opportunities. In this paper, we describe and analyse how displaced people employ these learning resources to complement, convert, and activate their educational (cultural, social, and symbolic) capital (Bourdieu, 1986) when (re)settling in a new place. We consider how during their time in Australia, participants’ patterns of utilising both informal and formal learning resources are neither linear nor homogenous and are subject to multiple adjustments along the way. We found that while there was no lack in learning resources available, their practical value in terms of capital conversion or activation was not immediately clear for these displaced people. To deal with this lack of information about the strategic value of different learning resources, our participants took up an array of informal and self-directed learning options, which proved useful both as pathways to more formal educational opportunities and as valuable sources of knowledge in themselves. Overall, in our participants’ experiences, a more accurate and timely informational guidance was needed to turn education into a valuable asset in (re)settlement.